Controversy about the Role of Children's Lawyers: Advocate or Best Interests Guardian? Comparing Practices in Two Canadian Jurisdictions with Different Policies for Lawyers. (21st October 2013) - Bala, Nicholas; Birnbaum, Rachel; Bertrand, Lorne
<x xml:space="preserve">Abstract</x> There is controversy about the role that lawyers for children should play in family proceedings, but little empirical research about what they actually do. This article reports on a study (n = 166) of the experiences and perspectives of lawyers in two Canadian provinces with different policies for the role of children's counsel. Official policies seem to have only a limited impact on the practices of lawyers for children, whether the policies direct lawyers to adopt a best interests guardian or a traditional instructional advocate role. Lawyers generally seem more comfortable adopting an instructional advocacy role, especially with older children. Lawyers who represent children comment on the deep satisfaction that they feel from this work. This article compares the practice of lawyers in the two jurisdictions on a number of issues related to child clients and proposes policy changes to provide better guidance and education for children's lawyers. Keypoints for the Family Court Community This survey of lawyers in these two jurisdiction reveals: lawyers spend longer meeting with older children; that official policies have some impact on the practice of lawyers, but a significant number of lawyers decide for themselves what role they will play; lawyers generally seem more comfortable adopting an instructional advocacy role, especially with older children; lawyers in the jurisdiction where they are expected to adopt a best interests role are more likely to tell parents and the court that they were adopting this role when they were in fact advocating what the child wanted; In both jurisdictions about one fifth of the lawyers reported that they had disclosed a child's "secret" to prevent harm to the child.